America and the Holocaust : a documentary history - Medoff, Rafael, 1959- (The Jewish Publication Society ; University of Nebraska Press, 2022)
"The first comprehensive volume to teach about America's response to the Holocaust through visual media, America and the Holocaust: A Documentary History explores the complex subject through the lens of 100 important documents that help illuminate and amplify key episodes and issues"--